Elementos religioso-bíblicos en fórmulas y documentos de época visigoda - Velázquez Soriano, Isabel (Antigüedad y Cristianismo, 1990)
This paper offers as material to analyse the echo that the religious elements, especially those of Biblical character, have in the formal langage of the legal documents by means of a brief rewiew of the Visigothic, Toronensic (etc.) collections of formulas. From the mere mention of God or Christ in the heading of the documents, or their invocation, to the quotation of Biblical passages, cited literally or in adapted form, includying the references to the Holy Texts although erroneous, are used as a note of distinction in the documents.